Personalized three-dimensional dosimetry of 32P patch brachytherapy for keloids using Monte Carlo simulation - Liu, Huan; Wen, Zhengwei; Tian, Feng; Li, Huanbin (Frontiers in Physics, 2026)
IntroductionKeloid brachytherapy using 32P patches demands precise dose calculation to achieve an optimal balance between therapeutic efficacy and clinical safety. Traditional dose calculation approaches frequently neglect patient-specific heterogeneous tissue compositions and anatomical morphology, which may result in inaccurate treatment planning and elevated recurrence risks. This study aims to develop a three-dimensional (3D) dose calculation method for 32P patch brachytherapy that incorporates individual anatomical and tissue characteristics.MethodsA voxelized phantom was constructed from the actual computed tomography (CT) images of keloid patients. The Monte Carlo (MC) Geant4 code was utilized to simulate the 32P patch brachytherapy procedure. A voxel-level dose calculation method was proposed and implemented to compute the average absorbed dose in keloids, and the 3D dose distribution within keloid lesions was subsequently obtained and evaluated.ResultsA total of 10 patient cases were analyzed. Significant variations in dosage parameters were observed across these cases, which could be attributed to the differences in keloid morphology and density composition. The minimum average absorbed dose in keloids was 1.62 × 10−4 mGy·MBq−1 (case 1), whereas the maximum average absorbed dose reached 9.31 mGy·MBq−4 (case 6). With respect to dose homogeneity, the Homogeneity Index (HI) values exhibited a wide range: the highest HI value was 326 (case 2), and the lowest was 4.68 (case 10), indicating a highly uneven dose distribution within keloids across the cohort.DiscussionThe results confirm that the proposed voxel-level dose calculation method enables more accurate and efficient assessment of 32P patch brachytherapy for keloids by integrating patient-specific anatomical features and tissue heterogeneity. This method underscores the critical importance of personalized treatment planning in optimizing dose delivery. Addressing the issue of uneven dose distribution can help balance therapeutic efficacy and safety, thereby providing a practical framework for reducing recurrence risks in clinical keloid brachytherapy.